2015
DOI: 10.1021/acs.jafc.5b04296
|View full text |Cite
|
Sign up to set email alerts
|

Talaromycolides A–C, Novel Phenyl-Substituted Phthalides Isolated from the Green Chinese Onion-Derived Fungus Talaromyces pinophilus AF-02

Abstract: The green Chinese onion (Allium fistulosum L.), which is widely cultivated and has been naturalized in many places, is an important spice and vegetable in East and Southeast Asia. It is used to treat the common cold in China. In the ongoing search for antibacterial activity in fungi derived from natural, pungently scented vegetables, the secondary metabolites of Talaromyces pinophilus AF-02, which was isolated from the stem of the green Chinese onion, were investigated. The genus Talaromyces (Trichocomaceae) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 28 publications
(59 reference statements)
0
25
0
Order By: Relevance
“…We used data from the PE library with an average insert size of 500 bp from T. pinophilus 1–95 to map the entire genome sequence of T. cellulolyticus Y-94 7 . The PE reads covered 35 scaffolds with 32.06 Mb of sequence from the T. cellulolyticus Y-94 genome, resulting in 88% average coverage and 83-times average depth (see Supplementary Table S4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used data from the PE library with an average insert size of 500 bp from T. pinophilus 1–95 to map the entire genome sequence of T. cellulolyticus Y-94 7 . The PE reads covered 35 scaffolds with 32.06 Mb of sequence from the T. cellulolyticus Y-94 genome, resulting in 88% average coverage and 83-times average depth (see Supplementary Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…These results suggested that T. pinophilus 1–95 has potential for producing bioactive secondary metabolites. Although thus far, several bioactive secondary metabolites have been extracted and characterized from T. pinophilus 6, 7 , according to the genomic data, additional secondary metabolites could be generated using this species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The species F. solani , F. oxysporum, C. perangustum , Cladosporium sp., T. pinophilus , P. coffeae , and M. verrucaria were dominant in this work, possibly due to the high spore production of these fungi and their cosmopolitan nature, which statistically increases their chance to become established as endophytes, as indicated in previous studies (Mishra et al., ; Raviraja, ; Schulthess & Faeth, ). In addition, based on the “balanced antagonisms” hypothesis (Schulz, Haas, Junker, Andree, & Schobert, ; Schulz, Rommert, Dammann, Aust, & Strack, ), they as dominant species might not only secrete toxic metabolites to inhibit microbial competitors (Breinholt et al., ; Lee & Lee, ; Zhai et al., ) but also possess the ability to resist the attack of the host alkaloids with antitumor and antifungal activities (Liu et al., ; Yang, Zhao, & Ju, ).…”
Section: Discussionmentioning
confidence: 99%
“…Three known diketopiperazines, cyclo( l -proline- l -leucine) ( 13 ), cyclo( l -proline- l -phenylalanine) ( 14 ), and cyclo( l -tyrosine- l -phenylalanine) ( 15 ), were isolated from the methanolic extracts of the green Chinese onion-derived fungus T. pinophilus AF-02 [ 7 ]. …”
Section: The Secondary Metabolitesmentioning
confidence: 99%